The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00128-009-9773-x
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Effects of Chiral Herbicide Diclofop Acid on Rice Xiushui 63 Seedlings

Abstract: In this study, the acute toxicity (72-h EC50 values) of chiral diclofop acid towards rice Xiushui 63 seedlings and its effects on the Hill reaction activities of chloroplasts were determined. Significant differences were observed between the two enantiomers in 72-h EC50 values and in both in vivo and in vitro relative Hill reaction activities. These observations indicate that the enantiomers of diclofop acid pose different toxicities to rice seedlings: the S-enantiomer is more toxic to leaves and the R-enantio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 18 publications
2
34
1
Order By: Relevance
“…The Hill reaction is known as the first step of photosynthesis, splitting of water to donate two electrons to the reaction center and can be used to evaluate photosynthetic capability (Ye et al 2009). Followed the extraction, the Hill reaction activity (HRA) of isolated chloroplasts under illuminating and dark condition in different concentrations was determined and compared.…”
Section: Chloroplast Extraction and Hill Reaction Activity Of Isolatementioning
confidence: 99%
“…The Hill reaction is known as the first step of photosynthesis, splitting of water to donate two electrons to the reaction center and can be used to evaluate photosynthetic capability (Ye et al 2009). Followed the extraction, the Hill reaction activity (HRA) of isolated chloroplasts under illuminating and dark condition in different concentrations was determined and compared.…”
Section: Chloroplast Extraction and Hill Reaction Activity Of Isolatementioning
confidence: 99%
“…The Hill reaction activity was measured according to Ye et al [19]. The reaction activity was calculated as the concentration of photo-reduced Fe(CN) 6 4− per mg chlorophyll per hour.…”
Section: Hill Reaction Activitymentioning
confidence: 99%
“…11 These studies demonstrated significant enantioselective toxicity of the chiral pesticides to plants. However, such a conclusion was drawn in most of these studies solely based on the different influence of enantiomers on the inhabitation of plant growth, with the exception of the research by Qian et al 11 and Ye et al, 12 which evolved enantioselective effects of enantiomers on antioxidant enzyme activity and the chloroplast Hill reaction. Recently, Liu et al 4 did an excellent review of the research in phytotoxicity of chiral plant growth regulators and chiral herbicides, in which they particularly emphasized the importance of the issues regarding the interactions between chiral compounds and plants.…”
Section: ' Introductionmentioning
confidence: 99%